HIGHER EDUCATION INSTITUTIONS STUDENTS HEALTHY LIFESTYLE DEVELOPMENT - Mallaeva Mavjudakhan Mahramovna; Khidirov Nemat Chorshanbievich; Kiyomov Ikhtiyor Ergashovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article examines directions for the development of a healthy lifestyle among students of higher education institutions, pedagogical observations from research, and the results, discussions and solutions of questionnaires.